A Randomised Control Trial for Comparative Evaluation of 3-D Versus 2-D Miniplates For Internal Fixation Of Mandibular Fractures - Sanjay Kumar; Nageshwar Iyer; Mansi Jain (University Library System, University of Pittsburgh, 2022)
Fracture of mandible is a common facial injury. For restoration of normal jaw structure and function, proper bony healing is important and thus, stable plate osteosynthesis has become an indispensable component of cranio-maxillofacial surgery. Aim: This study aimed to evaluate the efficacy of 3D versus 2D mini bone plates used for internal fixation of mandibular fractures. Methods and Material: A prospective randomised control trial was conducted on 20 patients with mandibular fractures in the symphysis and parasymphysis regions. In group 1, 3-D miniplates were used with a single, rectangular, 4-holed titanium plate with 4 screws and in group 2, 2-D miniplates were used with two 4-holed titanium plates fixed with 8 screws. Time taken for fixation and operators comfort was analysed using Chi square test whereas trismus and pain were analysed using Anova. Results: • The difference for mean time taken for fixation was statistically highly significant (P < 0.01) between 3-D (33.1 minutes) and 2-D plate( 44.7 minutes). • Fixation of 2-D plate was found more comfortable. • Swelling in both the groups was generally comparable and lasted for about 1 week. •  Mouth opening in patients of both the groups showed a gradual recovery till 1 month after which it stabilized. Conclusion: 3-D miniplate were more economical, with less intraoperative time required and showed better performance over 2-D miniplates. However there was difficulty in their adaption and were inappropriate when fracture line was very close to mental foramen.